Strategic training and development: the impact on employees’ performance / Idaya Husna Mohd, Joanna Julan and Tuan Badrol Hisham Tuan Besar - Mohd, Idaya Husna; Julan, Joanna; Tuan Besar, Tuan Badrol Hisham (Universiti Teknologi MARA, 2020)
Training and development are an essential strategic tool for enhancing employees’ performance and many organizations keep increasing training budget yearly basis with believe that it will earn them competitive advantage. The main objective of this study is to examine the impact of training and development on employees’ performance in a property management corporation. A total of one dependent variable; employees’ performance, and one independent variable, named training and development which consist of three dimensions; needs assessment, training and development techniques, and career development, have been developed. Quantitative and descriptive research methods are adopted for this particular study using one hundred valid questionnaires that were completed by the employees of this corporation. Simple random sampling technique is used and that the data collected are analyzed using descriptive statistics in order to represent the raw data in a meaningful manner. Based on the findings of this study employees believe that needs assessment should be done prior to deciding trainings, proper and suitable techniques are to be used to deliver trainings, and that further career development should be established in order to enhance employees’ performance.